2019
DOI: 10.3389/fchem.2019.00100
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrooxidation of Glycerol Into Value-Added Chemicals: A Short Overview

Abstract: A comprehensive overview of the catalysts developed for the electrooxidation of glycerol with the aim of producing selectively value-added compounds is proposed in the present contribution. By presenting the main results reported in the literature on glycerol electrooxidation in acidic and alkaline media, using different kinds of catalytic materials (monometallic catalysts based on platinum group metals and non-noble metals, multimetallic alloys, or modification of surfaces by adatoms, etc.) and under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 79 publications
1
120
0
4
Order By: Relevance
“…Special attention must be paid to polyoxomethalates, which have exhibited an interesting activity under mild conditions (60 • C), even with crude glycerol (Table 6), and could be supported as a catalyst modifier [190]. Another emerging option for performing room temperature oxidation processes is electrocatalysis due to its effective activity and selectivity to a specific compound, produced by tuning the structure of the electrocatalyst and/or the electrode potential [202][203][204][205]. Even though base addition is environmentally undesirable, in this process, whilst an inorganic base can act as an electrolyte for the reaction, other buffers can be applied [205].…”
Section: Glycerol Selective Oxidationmentioning
confidence: 99%
“…Special attention must be paid to polyoxomethalates, which have exhibited an interesting activity under mild conditions (60 • C), even with crude glycerol (Table 6), and could be supported as a catalyst modifier [190]. Another emerging option for performing room temperature oxidation processes is electrocatalysis due to its effective activity and selectivity to a specific compound, produced by tuning the structure of the electrocatalyst and/or the electrode potential [202][203][204][205]. Even though base addition is environmentally undesirable, in this process, whilst an inorganic base can act as an electrolyte for the reaction, other buffers can be applied [205].…”
Section: Glycerol Selective Oxidationmentioning
confidence: 99%
“…The reaction pathway for the glycerol electrooxidation in alkaline medium with C-C bond cleavage and in the absence of the oxidation of the secondary OH is shown in Figure 1 [2,10,[19][20][21][22][23][24]. Various reaction pathways were proposed for GLY oxidation to C2/C1 compounds (see Figure 1): in most of these pathways, GLA is the C3 compound that undergoes the breaking of one of two C-C bonds [10,[19][20][21][22][23], followed by TA [2,20,24], MOA [2,19] and also GLY [2], to form C2 and C1 compounds, while C2 compounds, such as GA [20], Glyoxylate (GOA) [21,24] and OA [24], undergo C-C bond cleavage to form FA and carbonate. Sandrini et al [25] reported that the GOR mechanism on Pt begins with glycerol dehydrogenation to alkoxydes followed by the formation of aldehyde intermediates adsorbed as η 1 (O)-aldehyde and η 1 (C)-acyl geometry, respectively.…”
Section: Pure Pt Pd and Au Catalysts And Binary Ptau And Pdau Catalystsmentioning
confidence: 99%
“…Glycerol oxidation on Pd lead to a selectivity towards GALD and GLA at low potentials, and then towards HPA, dicarboxylates and products derived by C-C bond cleavage (C2 and C1 compounds) at higher potentials [18,26]. It has to be denoted that the structure and morphology of the catalysts can play a role for the selectivity: GLA and TA were obtained on Pd/C, and HPA on Pd nanofoam [2].…”
Section: Pure Pt Pd and Au Catalysts And Binary Ptau And Pdau Catalystsmentioning
confidence: 99%
See 2 more Smart Citations